2022
DOI: 10.1002/mrm.29288
|View full text |Cite
|
Sign up to set email alerts
|

A patient‐friendly 16‐channel transmit/64‐channel receive coil array for combined head–neck MRI at 7 Tesla

Abstract: To extend the coverage of brain coil arrays to the neck and cervical-spine region to enable combined head and neck imaging at 7 Tesla (T) ultra-high field MRI. Methods:The coil array structures of a 64-channel receive coil and a 16-channel transmit coil were merged into one anatomically shaped close-fitting housing.Transmit characteristics were evaluated in a B 1 + -field mapping study and an electromagnetic model. Receive SNR and the encoding capability for accelerated imaging were evaluated and compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 41 publications
0
35
0
Order By: Relevance
“…Previously, multiple research groups demonstrated that a two-row combination of 16 loops (2 x 8) can be well decoupled 2,9,11 and provide a robust design for 3D RF shimming 9 of a whole human brain at 7 T. This approach has been previously used for designing both Tx-only 7-T volume coils (arrays) combined with smaller tight-fit multichannel Rx-arrays, that is, a so-called Tx-only/Rx-only (ToRo) setup, [13][14][15] and transceiver (TxRx) arrays, 9,16,17 in which all elements are used in both transmission and reception. Examples of 7-T ToRo human head arrays with 64 Rx-loops, 18,19 96 Rx-loops, 20 and potentially 128 Rx-loops, 21 have been reported.…”
mentioning
confidence: 99%
“…Previously, multiple research groups demonstrated that a two-row combination of 16 loops (2 x 8) can be well decoupled 2,9,11 and provide a robust design for 3D RF shimming 9 of a whole human brain at 7 T. This approach has been previously used for designing both Tx-only 7-T volume coils (arrays) combined with smaller tight-fit multichannel Rx-arrays, that is, a so-called Tx-only/Rx-only (ToRo) setup, [13][14][15] and transceiver (TxRx) arrays, 9,16,17 in which all elements are used in both transmission and reception. Examples of 7-T ToRo human head arrays with 64 Rx-loops, 18,19 96 Rx-loops, 20 and potentially 128 Rx-loops, 21 have been reported.…”
mentioning
confidence: 99%
“…Testing of this coil showed excellent performance over an extended range beyond the cervical spine including the occipital and upper thoracic regions when compared to other coils 5,6 . The Tx and Rx coils are integrated into a single housing equipped with hinges that allow it to be easily opened and closed to expedite the placement of the subject.…”
Section: Discussionmentioning
confidence: 91%
“…The SNR declines in the upper part of the studied region, which comprises most of the brain, but useful values were registered in the occipital region. Comparison to other coils (head and head-neck) with more channels demonstrated that 20 receive loops, with convenient dimensions and placement, were sufficient to obtain higher SNR along the spinal cord 5 . Average g-factors obtained during the same study over an axial plane positioned at level C3 of the cervical spine showed similar values for all coils up to acceleration factors (R) of 4, while reductions of 27% (0.67/0.49) and 22% (0.63/0.49), respectively, were observed for R=6.…”
Section: Comparison With Other Coilsmentioning
confidence: 97%
See 2 more Smart Citations